Torres strait governance structures and the centenary of Australian federation: a missed opportunity? - Sanders, Will (2000)
In his 1993 Boyer lecture, Getano Lui Jnr called for a change in the status of Torres Strait governance structures within the Australian federation, nominating the centenary of Federation on 1 January 2001 as a possible time for change. In 1996, the Commonwealth Minister for Aboriginal and Torres Strait Islander Affairs initiated a parliamentary committee inquiry into greater autonomy for the people of the Torres Strait, which reported favourably in 1997. This report was not, however, greeted all that favourably by Torres Strait Islanders and it now seems unlikely that any significantly new governance structures for Torres Strait will be in place by the centenary of Federation. This paper attempts to explain why. - Reproduced
Keywords: Local government - Australia; Local government